A population-based study of hospital care costs during 5 years after transient ischemic attack and stroke. - Luengo-Fernandez, R; Gray, A; Rothwell, P (2012)
BACKGROUND AND PURPOSE: Few studies have evaluated long-term costs after stroke onset, with almost no cost data for transient ischemic attack (TIA). We studied hospital costs during the 5 years after TIA or stroke in a population-based study. METHODS: Patients from a United Kingdom population-based cohort study (Oxford Vascular Study) were recruited from 2002 to 2007. Analysis was based on follow-up until 2010. Hospital resource usage was obtained from patient hospital records and valued using 2008/2009 unit costs. Because not all patients had full 5-year follow-up, we used nonparametric censoring techniques. RESULTS: Among 485 TIA and 729 stroke patients ascertained and included, mean censor-adjusted 5-year hospital costs after index stroke were $25,741 (95% confidence interval, 23,659-27,914), with costs varying considerably by severity: $21,134 after minor stroke; $33,119 after moderate stroke; and $28,552 after severe stroke. For the 239 surviving stroke patients who had reached final follow-up, mean costs were $24,383 (95% confidence interval, 20,156-28,595), with more than half of costs ($12,972) being incurred in the first year after the event. After index TIA, the mean censor-adjusted 5-year costs were $18,091 (95% confidence interval, 15,947-20,258). A multivariate analysis showed that event severity, recurrent stroke, and coronary events after the index event were independent predictors of 5-year costs. Differences by stroke subtype were mostly explained by stroke severity and subsequent events. CONCLUSIONS: Long-term hospital costs after TIA and stroke are considerable, but they are mainly incurred during the first year after the index event. Event severity and experiencing subsequent stroke and coronary events after the index event accounted for much of the increase in costs.